ANALISIS TERHADAP GARIS-GARIS BESAR HALUAN NEGARA SEBAGAI WUJUD PENGUATAN FUNGSI LEMBAGA MAJELIS PERMUSYAWARATAN RAKYAT REPUBLIK INDONESIA - Kalista, Dede Putra; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The urgency of the re-enactment of the GBHN was triggered due to thedisappointment of many parties related to the development process whose outputand output were not in accordance with what was mandated by the constitution.The development process is seen to be overemphasized on the limited perspectiveof the President or Regional Head elected, resulting in disparities in thedevelopment process in various regions. GBHN is mentioned as a manifestation ofsovereignty that is concrete in terms of its formation process, GBHN is mentionedas strengthening the principles of Check and Balances, GBHN is said to provecapable of realizing more successful, consistent and sustainable nationaldevelopment. The planning of development programs stipulated by the MPR in theGBHN has in fact not been realized systemically. The evaluation of the MPRbefore setting the last GBHN in the transition from the New Order government tothe reform era stated that development during the New Order era was onlyfocused on the economic sector and was not matched by progress in other sectors.Physically visible progress in the economic sector but fundamentally fragilebecause it does not have a clear legal basis, the law is far behind. Thus theassumption that chaos and lack of guidance in development in Indonesia hasactually been answered by the existence of RPJPN as a substitute for GBHN.Keywords: GBHN – Check and Balances – Fundamental Fragile